Examining the 8-Year Trajectory of Posttraumatic Stress Symptoms in Children Exposed to Intimate Partner Violence. Issue 15 (August 2021) - Galano, Maria M.; Grogan-Kaylor, Andrew; Clark, Hannah M.; Stein, Sara F.; Graham-Bermann, Sandra A.
Millions of children witness intimate partner violence (IPV) each year, and the effects of these experiences are substantial. One of the more common sequelae of exposure to IPV is the development of posttraumatic stress symptoms (PTSS). Given the chronic nature of both IPV and PTSS, there is a need for prospective research on long-term mental health outcomes following IPV exposure in childhood. This study prospectively examines trajectories of PTSS over an 8-year period, beginning from the preschool period. This study also investigates factors that may be associated with these trajectories, including intervention participation, continued IPV exposure, and the caregiving environment. A total of 120 mother–child dyads participated in four study waves over an 8-year period, beginning when children were between the ages of 4 and 6. Mothers and children participated in an intervention between baseline and Time 2. At the onset of the study, all mothers reported experiencing IPV over the previous year. Findings demonstrate that, in general, children experienced worsening of their PTSS over the 8-year trajectory, and few factors were significantly associated with this trajectory. There were no associations between intervention participation, parenting behaviors, and long-term child PTSS outcomes; however, there were significant associations between amount of IPV exposure, mother's level of PTSS, and children's PTSS outcomes. These results underscore the need to better understand the impact of early-life exposure to IPV, as well as the need for interventions tailored to this developmental period. Furthermore, these findings highlight the long-term negative associations between chronic exposure to IPV and child well-being, as well as the significant connections between caregiver and child mental health.